SmartWheel access solution / Nur Izzatul Fazzila Sanip … [et al.] - Sanip, Nur Izzatul Fazzila; Mohamad, Farzana Qistina Hazry; Mohammad Soffian, Farhah Batrisyia; Abdul Rahim, Najihah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Move Easy Sdn Bhd is introducing electronics wheelchair company founded by four young women entrepreneurs in Subang Jaya, Selangor. Our company aims to transform mobility solutions by blending innovative technology with user-centric design to enhance the lives of individuals with mobility challenges. Our company's building is located at Subang Jaya, Selangor. Our mission is to design and manufacture wheelchairs that are simple to use, easy to carry, and help people with disabilities feel more confident and free. Our vision to make life easier for people with disabilities by creating wheelchairs that are easy to use and help them move around more independently. we prioritize safety and security, offering wheelchairs equipped with safety features that provide greater confidence and security. Modern electronics wheelchairs are designed to ensure maximum comfort and reduce the risk of discomfort or injury from long usage. Move Easy Sdn Bhd offers voice-activated, hands-free control, personalized commands, smart connectivity, and enhanced accessibility for users with mobility challenges. With this, our company aims to enter the market with competitive pricing without compromising on the superior quality of its electronics wheelchairs, ensuring satisfaction for all users.